INVESTIGATION OF THE EFFECT OF MELATONIN ON HEMATOLOGICAL AND BIOCHEMICAL BLOOD PARAMETERS OF ANIMALS WITH TYPE 2 DIABETES (Experimental biology, 2023)
This article describes the effect of melatonin on changes in hematological and biochemical parameters in an experimental group of animals with type 2 diabetes. This study expands our knowledge of the impact of metabolic disorders on circadian rhythms, metabolic control, and homeostasis, and uses the nocturnal pineal hormone melatonin as a potential therapeutic agent for the prevention and treatment of diabetes. Therefore, the purpose of this study was to study changes in hematological and biochemical parameters in animals with type 2 diabetes mellitus using streptozocin, as well as to study the effect of the hormone melatonin on the quantitative analysis of total protein and electrolytes, including changes in protein in blood serum. The possible protective effect of melatonin on changes caused by type 2 diabetes mellitus has been studied in the general blood profile. An assessment of blood glucose and serum sugar levels confirmed the induction. I-main group: 1 - control animals (CA), 2 - control group animals are receiving 5 mg/kg of melatonin (CA + MT (5 mg/ kg)), 3 - control group animals are receiving 10 mg/kg of melatonin (CA + MT (10 mg/kg)). The experimental group of rats received an intravenous injection of streptozocin 1 mg in 0.1 M citrate buffer (pH-7.4) for 7 days. The leading group II of 24 rats with streptozocin-induced type 2 diabetes was divided into subgroups and subjected to various therapeutic procedures. Thus, group 4 – animals with induced type 2 diabetes mellitus (DM2T) served as diabetic control, and group 5 – animals with induced type 2 diabetes mellitus receiving low-concentration melatonin (DM2T+MT (5 mg/kg)), group 6 - diabetes-induced animals receiving high-concentration melatonin (DM2T+MT (10 mg/kg)). Abnormal hematological and biochemical parameters were detected in rats with diabetes mellitus. However, it was found that the introduction of melatonin leads to positive changes in hematological and biochemical parameters.